Not All Forms of Independence Are Created Equal: Only Being Independent the “Right Way” Is Associated With Self-Esteem and Life Satisfaction - Moza, Daniela; Lawrie, Smaranda Ioana; Maricuțoiu, Laurențiu P.; Gavreliuc, Alin; Kim, Heejung S. (Frontiers in Psychology, 2021)
Past research has found a strong and positive association between independent self-construal and life satisfaction, mediated through self-esteem, in both individualistic and collectivistic cultures. In Study 1, we collected data from four countries (United States, Japan, Romania, and Hungary; N = 736) and replicated these findings in cultures which have received little attention in past research. In Study 2, we treated independence as a multifaceted construct and further examine its relationship with self-esteem and life satisfaction using samples from the United States and Romania (N = 370). Different ways of being independent are associated with self-esteem and life satisfaction in the two cultures, suggesting that it is not independence as a global concept that predicts self-esteem and life satisfaction, but rather, feeling independent in culturally appropriate ways is a signal that one’s way of being fits in and is valued in one’s context.